Traffic-aware and low-overhead routing protocol for mobile ad hoc networks. (1st January 2013) - Awad, Fahed H.; Alsheakhali, Mohammad S.
In this paper, a new routing protocol for mobile ad hoc networks, called traffic-aware and low-overhead routing protocol (TALORP) is proposed. TALORP uses backup routes to mitigate the flooding problem that is frequently used to repair link failures. It also accounts for the traffic flows on different paths towards the destination in order to select the shortest and the least-congested path. The simulation results demonstrated that TALORP achieves better performance compared to similar protocols under a wide range of traffic conditions in terms of packet delivery ratio, end-to-end delay, and the average number of hops used but at the cost of increasing the routing overhead under certain traffic conditions.